2018
DOI: 10.1039/c8dt03951h
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of carbon dioxide with catechol- and pinacolborane using an Ir–CNP* pincer complex. Water influence on the catalytic activity

Abstract: Lutidine-derived CNP*–Ir complexes catalyze the hydroboration of CO2 to methoxyborane and formoxyborane in the presence of small amounts of water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 119 publications
1
17
0
Order By: Relevance
“…Recent research from our group has focused on the study of nonsymmetric lutidine-derived pincer ligands, i.e., having two inequivalent flanking donor groups, particularly of the CNP class (Figure ). The presence of two significantly different strong σ-donors in the CNP pincer, such as a phosphine and a NHC, allows a larger electronic and steric diversity of the ligands, and facilitates a direct comparison of the relative acid/base reactivities of the NHC- and phosphine-bound methylene arms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research from our group has focused on the study of nonsymmetric lutidine-derived pincer ligands, i.e., having two inequivalent flanking donor groups, particularly of the CNP class (Figure ). The presence of two significantly different strong σ-donors in the CNP pincer, such as a phosphine and a NHC, allows a larger electronic and steric diversity of the ligands, and facilitates a direct comparison of the relative acid/base reactivities of the NHC- and phosphine-bound methylene arms.…”
Section: Introductionmentioning
confidence: 99%
“…Upon deprotonation of the methylene CH 2 –NHC arms, these organometallics are catalytically active in ligand-assisted processes. 22 25 …”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Rendón, Suarez and co-workers showed that Ir carbonyl pincer complexes stabilized by a deprotonated lutidine-derived CNP* ligand selectively catalyzed the hydroboration of CO 2 under 1-2 bar, 30°C either to methoxyborane using HBcat (TOF = 56 h À 1 , maximum yield = 28 %, TON = 84) or to formoxyborane with the more sterically demanding HBpin (TOF = 1245 h À 1 ) in either THF/H 2 O or THF, respectively. [37] One year later, Hazari and co-workers examined the correlations between catalyst and borane structure and the level and rates of catalytic CO reduction using Pd and Ni complexes, supported by PSiP and PCP pincer ligands, varying systematically their steric and electronic properties ( Figure 1). [38] Results showed that a complex network of effects is active upon varying, together with the catalyst and the borane, the reaction conditions (CO 2 pressure, reaction time, catalyst concentration), ruling the activity and selectivity of the catalytic system.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the potential of Ir, Pd and Ni pincer complexes was examined in detail, focusing on the effects of type of ligands and hydroboranes in determining the selectivity of the reaction. In 2018, Rendón, Suarez and co‐workers showed that Ir carbonyl pincer complexes stabilized by a deprotonated lutidine‐derived CNP* ligand selectively catalyzed the hydroboration of CO 2 under 1–2 bar, 30 °C either to methoxyborane using HBcat (TOF=56 h −1 , maximum yield=28 %, TON=84) or to formoxyborane with the more sterically demanding HBpin (TOF=1245 h −1 ) in either THF/H 2 O or THF, respectively . One year later, Hazari and co‐workers examined the correlations between catalyst and borane structure and the level and rates of catalytic CO 2 reduction using Pd and Ni complexes, supported by PSiP and PCP pincer ligands, varying systematically their steric and electronic properties (Figure ) .…”
Section: Introductionmentioning
confidence: 99%